Virtual Inertia Control Topology Addressing Indonesia’s Low-Inertia Renewable Grid Resilience Challenge - F. Danang Wijaya; Fikri Waskito; Eka Firmansyah; Juan C. Vasques (This journal is published by the Department of Electrical and Information Engineering, Faculty of Engineering, Universitas Gadjah Mada., 2025)
The increasing penetration of renewable energy sources in Indonesia, particularly photovoltaic (PV) systems, into electric power grids has led to a reduction in system inertia, potentially compromising frequency stability during disturbances. This paper proposes a virtual inertia control method for single-phase rooftop PV inverters to enhance frequency response in low-inertia microgrids. A single-phase synchronverter model based on the swing equation was developed and tested on the IEEE 13-bus system. Three scenarios were evaluated: a solar-only microgrid, a wind-integrated microgrid, and a microgrid combining renewable sources with a synchronous generator. Simulation results demonstrated that the proposed virtual inertia method improved frequency and voltage stability, closely mimicking the response of traditional synchronous generators. Within the first 10 s following a disturbance, the system failed to restore its frequency to the nominal value due to insufficient inertia in the inertial response time range. This indicates that the initial 10 s are a critical period for frequency recovery. The poorest frequency response was observed in scenario 1 (solar-only configuration), where system inertia was the lowest among the three scenarios, while the hybrid configuration with a synchronous generator (scenario 3) provided the most stable and robust frequency performance. The findings support the recommendation to implement policies requiring rooftop PV systems to incorporate virtual inertia functionalities, ensuring greater system resilience as renewable energy penetration increases.